Changes in posttraumatic stress disorders symptoms during and after therapeutic community drug and alcohol treatment. Issue 4 (12th December 2016) - Perryman, Cassandra; Dingle, Genevieve; Clark, David
Abstract : Purpose: The purpose of this paper is to investigate the changes in posttraumatic stress disorder (PTSD) symptomatology during treatment in a drug and alcohol therapeutic community. Design/methodology/approach: A repeated measures design was employed that looked at PTSD, depression, anxiety, and stress at a pre- and post-timepoint. A second sample was then evaluated at time of program completion to seven months post-treatment. Findings: PTSD symptomatology significantly decreased in individuals who had undertaken treatment, and continued to decline post-treatment. This finding was irrespective of any PTSD-specific treatment. Research limitations/implications: PTSD specific treatment is not necessary to lower the symptomatology. Furthermore, this provides evidence that PTSD and substance use disorders are so highly intertwined that the comorbidity can almost be considered a single, diagnosis. Originality/value: This is a partial replication of previous research which had not previously been replicated. This research also adds to the limited research which looks at PTSD from the perspective of drug and alcohol rehabilitation.